A literature review of complementary and alternative medicine used among diabetes mellitus patients - Anita Joeliantina; Oedojo Soedirham; Mangestuti Agil; M. Bagus Qomaruddin; Kusnanto Kusnanto (Intelektual Pustaka Media Utama, 2019)
Diabetes is a chronic disease that requires regular and sustainable health management that involves proper treatment. Some diabetic patients use CAM, as well as conventional medicine, to maintain their health and control their blood sugar. This literature review aimed to 1) determine the prevalence of CAM used by patients with diabetes, summarize and evaluate the CAM use that includes: characteristics, patterns, types and reasons, 2) propose a conceptual model associated with CAM used by patients with diabetes. Systematic reviews were searched using an electronic database. The systematic reviews were published between 2005 and 2015 by using specific keywords. The number of systematic reviews obtained as a search result is 14 articles from 14 countries. The prevalence of CAM used by patients with diabetes ranged from 16.6% to 76%. Determinants associated with the CAM use were age, gender, family income, occupation, residence, and the characteristics of the disease, such as the length of time since diagnosed and complications. Most patients used CAM, along with the conventional treatment, and did not inform health professionals about the CAM use. The CAM use by patients with diabetes was relatively high and the confidence of patients believed the benefits of CAM. Therefore, integration with health professionals to develop CAM management is highly required.